Combined Foliar Zinc and Nitrogen Application in Broccoli (Brassica oleracea var. italica L.): Effects on Growth, Nutrient Bioaccumulation, and Bioactive Compounds - Angélica Rivera-Martin; Dolores Reynolds-Marzal; Alberto Martin; Rocio Velazquez; Maria J. Poblaciones (Agronomy, 2021)
To evaluate if the combined foliar application of nitrogen (N) and zinc (Zn) in broccoli improves the efficiency of the single Zn biofortification, five treatments were tested: (i) control; (ii) one Zn application at the beginning of flowering (0.5M1); (iii) combined 0.5M1 with N application (0.5M1N); (iv) two Zn applications, one at the beginning of the flowering and other after two weeks (0.25 + 0.25) and (v) combined 0.25 + 0.25 with N (0.25N + 0.25N). The Parthenon cultivar showed a good concentration of Ca, Fe, Mg, and Zn, with good bioavailability and glucosinolates, mainly in the florets, and high antioxidant activity and total phenols, mainly in the leaves, showing their potential not only as regards to human consumption, but also for the use of their by-products. All the studied treatments increased floret growth (19%), antioxidant capacity and total phenol content, not affecting Ca, Fe, and Mg concentrations. Glucosinolate content was mostly independent from the studied treatments, decreasing slightly in terms of glucoiberin and the Zn concentration in the florets increased in >50 mg Zn kg−1 in the split treatments and ~40 mg Zn kg−1 when the application was unique, with excellent bioavailability, measured as PA:Zn ratio. Therefore, 0.25 + 0.25 and 0.25N + 0.25N applications have been confirmed as the applications that improve more both growth and accumulation of Zn and biocompounds in broccoli.